The Relationship Between Parents’ Knowledge of Oral and Dental Health Maintenance and the Oral Hygiene Status of Visually Impaired Students at SMPLB-A and SMALB-A YPAB Surabaya - Shelani Krisdayana Safitri; Isnanto; Sri Hidayati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Children with visual impairments are particularly vulnerable to poor oral hygiene due to limitations in visual perception and motor coordination, which hinder their ability to perform effective self-care. As a result, parental involvement plays a critical role in maintaining their oral and dental health. However, limited parental knowledge regarding appropriate oral health practices may contribute to inadequate hygiene outcomes in this population. This study aimed to examine the relationship between parents’ knowledge of oral and dental health maintenance and the oral hygiene status of visually impaired students at SMPLB-A and SMALB-A YPAB Surabaya. A descriptive correlational study with a cross-sectional design was conducted involving 24 visually impaired students and their parents, selected through total sampling. Parental knowledge was assessed using a structured and validated questionnaire covering tooth-brushing techniques, appropriate brushing times, and dental care practices. The oral hygiene status of the students was evaluated clinically using the Simplified Oral Hygiene Index (OHI-S). Data were analyzed using the Spearman rank correlation test to determine the association between parental knowledge and children’s oral hygiene status. The results revealed that the majority of parents had a moderate level of oral health knowledge (58.3%), while only 33.3% demonstrated high knowledge. None of the students achieved a “good” oral hygiene status; 33.3% were categorized as “fair,” and 66.7% as “poor.” The mean OHI-S score was 3.49, exceeding the national target value of ≤1.2. Statistical analysis showed a strong and significant correlation between parental knowledge and oral hygiene status (ρ = 0.848; p < 0.05). In conclusion, higher parental knowledge of oral and dental health maintenance is strongly associated with better oral hygiene outcomes among visually impaired children. These findings highlight the need for targeted oral health education programs for parents to improve preventive care and oral health status in this vulnerable group.